1996
DOI: 10.1021/ja9532998
|View full text |Cite
|
Sign up to set email alerts
|

Luminescence Quenching in Supramolecular Systems:  A Comparison of DNA- and SDS Micelle-Mediated Photoinduced Electron Transfer between Metal Complexes

Abstract: Photoinduced electron transfer reactions between photoexcited Ru(phen)2dppz2+ (phen = 1,10-phenanthroline, dppz = dipyridophenazine) and acceptors Rh(phi)2bpy3+ and Rh(phen)2phi3+ (phi = 9,10-phenanthrenequinone diimine, bpy = 2,2‘-bipyridine) are compared in micelles and DNA. Both microheterogeneous environments contain a negatively charged surface and hydrophobic interior and the cationic complexes associate strongly with each. However, reactions between molecules bound to DNA or to micelles show striking di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
98
0

Year Published

1999
1999
2013
2013

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 164 publications
(104 citation statements)
references
References 71 publications
6
98
0
Order By: Relevance
“…A binding ratio is defined as the concentration ratio of the binding ligand to total ligand [6], and the binding number is regarded as the number of participating DNA sites [7]. The interaction of DNA with drugs has been studied by various techniques including fluorescence [8], UV-vis [9], FT-IR [10], luminescence [11], capillary electrophoresis [12], NMR [13], microgravimetry [14], electroanalytical methods [15] and surface plasmon resonance [16]. Voltammetry has also been used to study such interactions [17 -20], and the observed electrochemical signals can provide useful information about the interaction mechanism, binding constant and binding forces.…”
Section: Introductionmentioning
confidence: 99%
“…A binding ratio is defined as the concentration ratio of the binding ligand to total ligand [6], and the binding number is regarded as the number of participating DNA sites [7]. The interaction of DNA with drugs has been studied by various techniques including fluorescence [8], UV-vis [9], FT-IR [10], luminescence [11], capillary electrophoresis [12], NMR [13], microgravimetry [14], electroanalytical methods [15] and surface plasmon resonance [16]. Voltammetry has also been used to study such interactions [17 -20], and the observed electrochemical signals can provide useful information about the interaction mechanism, binding constant and binding forces.…”
Section: Introductionmentioning
confidence: 99%
“…the CMC, their aggregation number (n), their size. The most frequently applied methods to determine aggregation number are various scattering methods and fluorescence quenching (FQ) method [11][12][13][14][15][16][17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…8,15,20,[40][41][42][43][44][45] The difference between the donor and acceptor standard potentials (∆E°), standard free energy of transfer (∆G), and reorganization energy (λ), shown in Figure 2, determine the energetics of the reaction. These quantities are determined by solute energy levels, local dielectric properties, and molecular sizes and charges.…”
Section: Introductionmentioning
confidence: 99%